Investigation and analysis of Banoo Ghasseb's personality in Banoo Ghasseb letter system According to the theory of creative women from Estes - Jalali Ghasempour, Farahnaz (2021)
In recent decades, various theories and movements have been formed regarding women and their role in human society, and a number of experts have sought to eliminate gender stereotypes arising from patriarchal culture. They have been identifying women. Among them is Clarissa Pincola Estes, who has taken an important step in achieving dignity for women with her theory of creative women. In the field of classical Persian literature, despite the dominance of patriarchal culture, in some cases we have witnessed the emergence of women who have broken social norms and tried to achieve an identity independent of men. Rostam Dokhtar's lady is one of these women whose thoughts and behaviors are mentioned in the's poem. In this research, with reference to library resources and descriptive-analytical method, as well as the use of components of the theory of creative women from Estes, the characteristics of Banu Ghasseb have been studied and described. The results show that this woman has an independent female personality and has made efforts to combat the culture of male monologue. His negative reaction to love and marriage to Gio, the killing of Tamratash Turani, the fight against Rustam and the Indian suitors are some of the manifestations of this effort. With complete self-knowledge, the use of creativity, as well as awareness of her physical abilities, she transforms feminine passivity and stagnation into dynamism, and with an unyielding spirit, a laudable attempt to eliminate the unfavorable life situations. Had. Creativity in Banoo Ghasseb's personality has two external (invention of needlework) and internal (resistance to authoritarian men).